Conducting research in a resource-constrained environment: avoiding the pitfalls - Janine I. Munsamy; Andy Parrish; Gavin Steel (PAGEPress Publications, 2014)
Practical challenges affected the conducting of a retrospective drug use evaluation (DUE) on the rational use of tenofovir in a resourceconstrained South African Antiretroviral Treatment Programme. The primary outcome measure was the percentage of patient records compliant with DUE criteria using initiation prescriptions from March 2009 to February 2010. Health system challenges encountered included stringent institutional administrative procedures, lack of efficient communication channels, reliance on overburdened personnel and fear of audit. Forty percent (222 of 556) of patient records identified for inclusion in the study had to be excluded, mainly due to poor record keeping. Research budgetary constraints also limited data collection. This experience highlighted real, unforeseen challenges when conducting a retrospective study in a resource-constrained environment. A sound understanding of the environment and adequate preparation is recommended. The lessons learnt may prove valuable to both firsttime and experienced researchers in a resource-limited setting using a similar methodology.